Pemicu Pelecehan Seksual pada Perempuan - Natasya Dwi Nanda; Bimillati Arifanny Ikhwana; Jasmine Az-Zahra (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
Data on the high rate of violence against women in Indonesia is indeed a very important concern. The use of qualitative methods in this study made it possible to delve into them in more detail, providing insight into the more substantial aspects of the issue. Factors such as a strong patriarchal culture and low public awareness of violence against women can indeed be the main causes of this situation. Understanding these factors can help in overcoming existing problems. Finding ways to raise public awareness, strengthen legal protections for victims, and provide appropriate psychological assistance to victims can be necessary steps to reduce the rate of violence against women.